2015
DOI: 10.1590/0047-2085000000058
|View full text |Cite
|
Sign up to set email alerts
|

Estudos psicométricos de instrumentos breves de rastreio para múltiplos transtornos mentais

Abstract: RESUMOObjetivo: Realizar uma revisão sistemática sobre as características psicométricas de instrumentos breves para rastreamento de múltiplos transtornos mentais em cuidados primários de saúde. Métodos: Revisão sistemática da literatura nas bases de dados PubMed, Lilacs, SciELO e ISI, de artigos publicados até abril de 2014, utilizando descritores sobre rastreamento breve de múltiplos transtornos mentais em cuidados primários de saúde. Resultados: Foram obtidos 277 estudos e selecionados 15 após a aplicação do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 24 publications
0
13
0
4
Order By: Relevance
“…Moreover, EBADEP-A might also serve an initial indicator of the presence or absence of depressive disorder. Similarly, a short version of the instrument is presented in this study for the first time, which provided similar indices of diagnostic accuracy, suggesting its adequacy for screenings in which the professional has little time to perform assistance and/or does not need further information regarding the symptoms of depression, since short versions can be very useful in screening assessments (Bolsoni & Zuardi, 2015). It can be concluded that the short version of EBADEP-A was equivalent to its full version, that is, not inferior to it.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Moreover, EBADEP-A might also serve an initial indicator of the presence or absence of depressive disorder. Similarly, a short version of the instrument is presented in this study for the first time, which provided similar indices of diagnostic accuracy, suggesting its adequacy for screenings in which the professional has little time to perform assistance and/or does not need further information regarding the symptoms of depression, since short versions can be very useful in screening assessments (Bolsoni & Zuardi, 2015). It can be concluded that the short version of EBADEP-A was equivalent to its full version, that is, not inferior to it.…”
Section: Discussionmentioning
confidence: 72%
“…The use of abbreviated scales, called "short versions," has been usual, since they are less costly and save time, provided that they meet psychometric quality standards, such as sensitivity and specificity values near those of the longer or reference scales (i.e., gold standards). Moreover, according to Bolsoni and Zuardi (2015), screening scales for mental disorders with fewer items may be very useful in primary health care.…”
mentioning
confidence: 99%
“…A não identificação de uma comorbidade implicará resposta parcial ao tratamento 39 . No campo da atenção primária, isso se torna mais relevante ao considerar que não há especialistas na área e não são usados rotineiramente instrumentos de avaliação para a detecção dos transtornos mentais 40 . Estudos mostram que a melhora na detecção de tais transtornos no nível primário pode incidir em diminuição na procura por atendimento médico e na utilização de recursos em saúde, o que contribuiria para desonerar o sistema de saúde 41,42 .…”
Section: Discussionunclassified
“…Dessa forma, de acordo com a revisão sistemática apresentada (Bolsoni;Zuardi, 2015), bem como outros estudos disponíveis (de Azevedo Marques, e Zuardi, 2011;Pollard et al, 2013), conclui-se que são raros os instrumentos de rastreio que são breves e que avaliam múltiplos transtornos mentais, incluindo transtornos mentais mais comuns (depressão e ansiedade), abuso de substâncias e quadros psicóticos, sendo quadros de grande relevância de saúde pública.…”
Section: Instrumentos De Rastreiounclassified
“…Estudo de revisão bibliográfica sobre qualidades psicométricas de instrumentos breves de rastreio para múltiplos transtornos mentais (Bolsoni;Zuardi, 2015) evidencia a carência na literatura de instrumentos breves e fidedignos que rastreiam múltiplos transtornos mentais. Na tabela 3, destacar-se-á: a) instrumento de rastreio; b) técnica para calculo de fidedignidade empregada e, c) valor de fidedignidade: Para outros instrumentos, tais como: FSQ, HDI e BHM, a fidedignidade foi avaliada para construtos específicos do teste em questão (Jette et al, 1986;Saunders et al, 2004;Bryan et al;.…”
Section: Validação Dos Instrumentos De Rastreiounclassified